THIRTY YEARS OF TEFLIN JOURNAL: A BIBLIOMETRIC PORTRAIT THROUGH THE LENS OF MICROSOFT ACADEMIC - Syahid, Abdul; Mukminatien, Nur (TEFLIN Journal, 2021)
To examine bodies of literature from the levels of topics, regions, nations, and journals, a lot of bibliometric studies have been conducted in many fields. However, such studies are a rare undertaking in the field of English language teaching, especially at a journal level. To celebrate the TEFLIN Journal's 30th anniversary, this study exhibits a bibliometric portrait of its publication, indexation, and citation from 1990 to 2019. Two pieces of free software, Publish or Perish and VOSviewer were adopted to conduct the descriptive and network analyses of bibliographic data from Microsoft Academic. In terms of 19 out of 27 metrics in Publish or Perish software, the journal's publication and citation metrics have risen during its lifetime. The bibliographic network identifies the most productive authors, institutions, and countries along with the co-authorship pattern, type of top-cited articles, and top-used keywords. The article relatedness is also sighted in terms of the citation frequency and number of shared references. Even though the analyses were complicated by some missing articles and improper indexation, this study could still take a full-length bibliometric portrait of the journal during its 30-year journey between the commitment to competence and the quest for higher impact.